The 2003 Presidential Address of the CHA: The Mass Media in Canadian History: The Empire Day Broadcast of 1939 - Vipond, Mary (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractSince the seminal works of Harold Innis, communication has been a major theme in Canadian history and historiography. Internationally as well, scholars such as Benedict Anderson, Karl Deutsch and John B. Thompson have recognized the centrality of communication systems, particularly the mass media, to the development of the modern world. Unfortunately Canadian historians have not shown much interest in studying the mass media as a formative force in modern Canadian history. Data from the CHA's Register of Dissertations are used to demonstrate the paucity of graduate student research, especially about broadcasting, and some explanations for the neglect are proffered. The paper concludes with an examination of the CBC's Empire Day Broadcast, a central event of the Royal Tour of 1939. This case study demonstrates how one mass media institution worked to construct identity and evoke tradition. It illustrates some of the linkages between the history of the mass media and other current preoccupations of historians, including cultural history (especially the study of spectacles and commemorations) and imperial history (relationships within the British-North American world as World War II approached).